Biphasic alteration of the inhibitory synapse scaffold protein gephyrin in early and late stages of an Alzheimer disease model - Kiss, Eva; Gorgas, Karin; Schlicksupp, Andrea; Groß, Dagmar; Kins, Stefan; Kirsch, Joachim; Kuhse, Jochen (The American journal of pathology, 2016)
The pathogenesis of Alzheimer disease (AD) is thought to begin many years before the diagnosis of dementia. Accumulating evidence indicates the involvement of GABAergic neurotransmission in the physiopathology of AD. However, in comparison to excitatory synapses, the structural and functional alterations of inhibitory synapses in AD are less well characterized. We studied the expression and distribution of proteins specific for inhibitory synapses in hippocampal areas of APPPS1 mice at different ages. Interestingly, by immunoblotting and confocal fluorescence microscopy, we disclosed a robust increase in the expression of gephyrin, an organizer of ligand-gated ion channels at inhibitory synapses in hippocampus CA1 and dentate gyrus of young presymptomatic APPPS1 mice (1 to 3 months) as compared to controls. The postsynaptic γ2-GABA(A)-receptor subunit and the presynaptic vesicular inhibitory amino acid transporter protein showed similar expression patterns. In contrast, adult transgenic animals (12 months) displayed decreased levels of these proteins in comparison to wild type in hippocampus areas devoid of amyloid plaques. Within most plaques, strong gephyrin immunoreactivity was detected, partially colocalizing with vesicular amino acid transporter and GABA(A)-receptor γ2 subunit immunoreactivities. Our results indicate a biphasic alteration in expression of hippocampal inhibitory synapse components in AD. Altered inhibition of neurotransmission might be an early prognostic marker and might even be involved in the pathogenesis of AD.
Gesehen am 13.05.2020